STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN DITOKO METRO STORE DAN FASHION BANYUANYAR – PROBOLINGGO - Rofiah, Tri Nadhirotur Rofiah; Fadil, Nurul; Hoirunnas (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
The purpose of this research is to examine the problems and to find out the promotional strategies carried out by the Metro Store and Fashion Stores in Klenang Kidul Village, Banyuanyar District, Probolinggo Regency through direct exposure systems, promos, WhatsApp and Instagram.  To find out the factors that can increase sales at the Metro Store and Fashion Stores in Tarokan Village, Banyuanyar District, Probolinggo Regency. This research is a field research, namely research in which data information is obtained directly in the field. The method used in this research is a qualitative method, which is a research aimed at describing and analyzing phenomena, events, activities, social, attitudes, beliefs, perceptions, thoughts, people individually and in groups. The Metro Store and Fashion store is using a promo strategy, direct exposure, WhatsApp and Instagram.  This strategy yielded many improvements once it was implemented.  Because customers can enjoy the right price.  very good service that can support customers to return to buy goods that have been provided at the Metro Store and Fashion stores.  For strategies that use WhatsApp and Instagram, there are no less buyers.  Because now it's time to use technology, via watsap there is already 1 grub and there is already someone who manages it starting from the Maron, Gending, Banyuanyar, Ranu Gedang Tiris areas for via Instagram only managed by people.  Because most people don't use Instagram, those who manage WhatsApp media have gone directly to the field and socialized the products in the Metro Store and Fashion Stores. The factors that increase sales at the Metro Store and Fashion stores are the first to ensure that products are in accordance with market needs, the second makes it easier for customers to recognize product advantages, the third maximizes technology that can drive sales, the fourth is the price factor, the fifth is the strategy factor, the sixth is the service factor.